2018
DOI: 10.20944/preprints201811.0445.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Comparative Evaluation of the Microbial Safety of Boiled Locally Vended Ready-to-Drink, HTST Pasteurized and UHT Bovine Milk Sold in Nakawa Division of Metropolitan Kampala

Abstract: This study evaluated the microbial safety of vended boiled, pasteurized and UHT milk sold in Nakawa, Kampala-Uganda. 15 milk samples were analyzed; 2 samples had Salmonella, 5 had S. aureus with a count of 1.66 0.02 log10CFU/ml. E. coli was detected in 8 samples with 1.0 0.02 to 3.0 0.01log10CFU/ml count. A high load of 3.0 CFU/ml was obtained in 3 samples with E. coli. Four E. coli positive samples had a contamination load of 2.0 0.015log10 CFU/ml of which one was pasteurized milk. Only a pasteurized milk sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…AFM 1 is detectable in milk 12-24 hours after the first AFB 1 ingestion, reaching a high level after a few days. us, dietary exposure to AFs through consumption of milk from lactating animals fed on AF-contaminated feeds in Uganda is as high as microbial contamination of milk reported in Metropolitan Kampala [84]. In Western Uganda, Kitya et al [57] reported that a bovine milk-based ghee sauce (Eshabwe) had a mean total AF content of 18.6 ± 2.4 μg/kg which was the highest of all the matrices tested for AFs in the Ankole districts of Mbarara, Ntungamo, Rukungiri, Kasese, and Kabale (Table 4).…”
Section: Animal Productsmentioning
confidence: 99%
“…AFM 1 is detectable in milk 12-24 hours after the first AFB 1 ingestion, reaching a high level after a few days. us, dietary exposure to AFs through consumption of milk from lactating animals fed on AF-contaminated feeds in Uganda is as high as microbial contamination of milk reported in Metropolitan Kampala [84]. In Western Uganda, Kitya et al [57] reported that a bovine milk-based ghee sauce (Eshabwe) had a mean total AF content of 18.6 ± 2.4 μg/kg which was the highest of all the matrices tested for AFs in the Ankole districts of Mbarara, Ntungamo, Rukungiri, Kasese, and Kabale (Table 4).…”
Section: Animal Productsmentioning
confidence: 99%
“…Uganda, the pearl of Africa [63] is a landlocked country straddling the equator in Eastern Africa. It is flanked by Lake Victoria, Tanzania and Rwanda to the south, Kenya to the East, South Sudan to the North and Democratic Republic of Congo to the West (Figure 2).…”
Section: Description Of the Study Areamentioning
confidence: 99%
“…While fermented milk is also a product that is in demand because of its usefulness to the digestive system. So for the selection of pasteurized milk products tend to be less desirable because of constraints on the distribution channel (Omara et al, 2018). Pasteurized milk which requires the presence of a cold chain (cooling lane), tends to be durable and easily damaged.…”
Section: Introductionmentioning
confidence: 99%